Evaluation of a 38 L Explosive Chamber for Testing Coal Dust Explosibility. (2nd September 2019) - Eades, Robert; Perry, Kyle
Abstract : Coal dust explosions are the deadliest disasters facing the coal mining industry. Research has been conducted globally on this topic for decades. The first explosibility tests in the United States were performed by the Bureau of Mines using a 20 L chamber. This serves as the basis for all standardized tests used for combustible dusts. The purpose of this paper is to investigate the use of a new 38 L chamber for testing coal dust explosions. The 38 L chamber features design modifications to model the unique conditions present in an underground coal mine when compared to other industries where combustible dust hazards are present. A series of explosibility tests were conducted within the explosive chamber using a sample of Pittsburgh pulverized coal dust and a five kJ Sobbe igniter. Analysis to find the maximum pressure ratio and K st combustible dust parameter was performed for each trial. Based upon this analysis, observations are made for each concentration regarding whether the explosibility test was under-fueled or over-fueled. Based upon this analysis, a recommendation for future explosibility testing concentrations is made.